ANALYSIS OF SLOW FREON CONDENSATION ON THE CONDENSOR OF FOOD COOLERING MACHINES TO SUPPORT THE SUSTAINABILITY OF DAILY ACTIVITIES ON THE MV. BOGA INDAH SHIP - Hartaya, Hartaya; Suhartini, Suhartini; tyo bagas pamungkas, Eggi (Dinasti Publisher, 2021)
One of the most vital supports related to welfare and health is the Refrigeration Machine to ensure the quality and quantity of food ingredients. For meat and fish that is still good is the meat and fish are not mushy, not rotten and when stored can freeze completely and if necessary crystallize. In order for foodstuffs to remain good, they need a storage temperature of ± 2?. For the storage of meat and fish we need a storage temperature of ± 15?. The less than optimal working of the cooling machine is influenced by various factors, both internal factors such as the number of hours the machine works. For external factors, this is closely related to the lack of maintenance on the cooling machine. In the research that the author did, there were several factors that were very influential in the smooth operation of the food cooling machine. The presence of frost on the evaporator pipes is a problem that most often occurs in the work of the evaporator. This happens when the pipe surface temperature is lower than 00 (freezing temperature of water). Next is the lack of good condensation process. The suggestions given in this problem are: Immediately close the cooling room door when entering or leaving the cooling room and monitoring and periodical maintenance of the amount of freon through the guessing glass and lubricating oil contained in the compressor. So that the freon condensation process is perfect and can meet the cooling needs, then do the condenser maintenance properly. For normal conditions once a month and if in an emergency condition can be cleaned and checked as soon as possible.